PHARMACOKINETIC PROFILE OF TETRAPRENYLTOLUQUINONE AFTER SINGLE-DOSE ORAL ADMINISTRATION IN MALE MICE - SUSANTI, MERI; FRAWIRA, REZA YUDA; DACHRIYANUS; WAHYUNI, FATMA SRI (International Journal of Applied Pharmaceutics, 2023)
Objective: The aim of this study to investigate pharmacokinetic profile of tetraprenyltoluquinone (TPTQ) in male mice’s blood plasma. Methods: A single dose of 800 mg/kg carried by Virgin Coconut Oil (VCO) was given orally where VCO only also administered as a control. Bloods were collected from vena jugularis after 0, ½, ¾, 1, 1½, 2, 3, 4, 6, 8, 12, and 24 h. The TPTQ levels in plasma were analyzed using High-Performance Liquid Chromatography (HPLC) following pre-treatment to induce protein precipitation. Results: The formed pharmacokinetic profile follows the two-compartment model where TPTQ levels increase during the absorption phase and form a biphasic pattern after it decrease. The results showed the pharmacokinetic parameters had Cmax value of 154.92±19.55 µg/ml at tmax of 1.117 h with AUC0-∞ of 1067.59 µg. h/ml. Other parameters were also obtained such as ka = 1.448±0.17 h-1, α = 0.511±0.07 h-1, ke = 0.057±0.02 h-1, t½ absorption = 0.483±0.05 h, t½ elimination = 12.131±0.55 h, Vd/F = 5284.79±629.49 ml, dan Cl/F = 751.84±53.85 ml/h. Conclusion: The pharmacokinetic profile of TPTQ administered orally show that TPTQ absorbed rapidly, eliminated slowly, and also distributed to peripheral tissues.